In Vitro Antibacterial Activities and Calf Thymus DNA–Bovine Serum Albumin Interactions of Tridentate NNO Hydrazone Schiff Base–Metal Complexes - Maida Katherine Triviño-Rojas; Santiago José Jiménez-Lopez; Richard D’Vries; Alberto Aragón-Muriel; Dorian Polo-Cerón (Inorganics)
Their demonstrable bioactive characteristics, coupled with their wide structural diversity and coordination versatility, render Schiff bases and their coordination complexes biologically active compounds demonstrating outstanding properties. This research describes the synthesis and characterization of new Cu(II) and Ni(II) complexes with an NNO-donor hydrazone ligand (HL). The crystal structure of the HL ligand was determined through single-crystal X-ray diffraction studies. The in vitro antibacterial activities of the HL ligand and its metal(II) complexes against Gram-positive and Gram-negative bacteria demonstrated that the metal(II) complexes displayed greater antimicrobial activities compared to the free Schiff base ligand. Furthermore, the interaction of the ligand and the complexes with calf thymus DNA (CT-DNA) was explored through electronic absorption and viscosity measurements, suggesting intercalation as the most likely mode of binding. The compounds promoted oxidative DNA cleavage, as demonstrated by the strand breaks of the pmChery plasmid under oxidative stress conditions. Finally, fluorescence spectroscopy also revealed the strong binding affinity of these compounds for bovine serum albumin (BSA).